Measuring foot pressure in pointe shoes of ballet dancers using a modified foot pressure sensor: a brief study - Sato, N.; Oba, N.; Seki, H.; Miura, A. (Journal of Dance Medicine & Science, 2026)
Introduction: The mechanism of foot injury in ballet dancers can be understood by measuring the forces exerted on the foot in pointe shoes. In this study, we aimed to reveal the vertical forces applied to the toes in a pointe shoe during ballet movements in a time series using a modified foot pressure sensor.